EGMR 1760/15 vom 30. April 2019 , CASE OF T.B. v. SWITZERLAND - [German Translation] summary by the Austrian Institute for Human Rights (ÖIM) - Hudoc Ch (2019)
Violation of Article 5 - Right to liberty and security (Article 5-1 - Lawful arrest or detention;Procedure prescribed by law); Violation: 5;5-1